2003
DOI: 10.1056/nejmsa022615
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Health Care Delivered to Adults in the United States

Abstract: The deficits we have identified in adherence to recommended processes for basic care pose serious threats to the health of the American public. Strategies to reduce these deficits in care are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

64
2,720
5
50

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 4,391 publications
(2,839 citation statements)
references
References 42 publications
64
2,720
5
50
Order By: Relevance
“…Low adherence to quality indicators for treating various diseases has been found in many US health care systems (6,7), particularly for treatment of musculoskeletal diseases including rheumatoid arthritis (8), acute low back pain (6), and osteoarthritis (9), with quality scores ranging from 54% to 65%. MacLean et al (8) studied patients with rheumatoid arthritis enrolled in a nationwide US insurance company and reported quality scores of 62% for arthritis care, 52% for comorbid disease care, and 42% for health care maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Low adherence to quality indicators for treating various diseases has been found in many US health care systems (6,7), particularly for treatment of musculoskeletal diseases including rheumatoid arthritis (8), acute low back pain (6), and osteoarthritis (9), with quality scores ranging from 54% to 65%. MacLean et al (8) studied patients with rheumatoid arthritis enrolled in a nationwide US insurance company and reported quality scores of 62% for arthritis care, 52% for comorbid disease care, and 42% for health care maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…46,47 For example, Birkmeyer et al showed the ratio of the highest to the lowest hospital referral regions for carotid endarterectomy for Medicare enrollees in the USA to be approximately 10 to 1. 46 Variation based on differences between patients is appropriate, but this variation was not explained by case mix or even by differences in resource.…”
Section: Variation In Health Carementioning
confidence: 99%
“…46,47 Par exemple, Birkmeyer et coll. ont montré que l'incidence de consultations pour une endartériectomie carotidienne pour les patients inscrits à Medicare aux É tats-Unis variait d'un facteur d'à peu près 10 entre la région ayant la plus grande incidence et celle dont l'incidence était la plus faible.…”
Section: Les Variations Dans Les Soins De Santéunclassified
“…3 In the 14 years since Donabedian's death, the quality landscape has changed markedly and has moved from a more general awareness of quality chasms in health care to broader policy efforts designed to proactively assess quality and improve care. [4][5][6][7][8] Central to these efforts, the best way to measure quality is as pertinent a question today as it was in 2000. Resoundingly, however, structure, process, and outcome measures that evaluate the context and setting of care, the way in which care is delivered, and the effects of that care have become the main linchpins in quality assessment and improvement programs.…”
mentioning
confidence: 99%